The Evaluation Of The Leadership Role Of School Principal - Miranda, Pedro da Costa; Iriani, Ade (Universitas Negeri Malang, 2021)
This study aims to evaluate the leadership role of school principals in Ensino Secundario Geral Cristal. This type of research is descriptive qualitative by using the Discrepancy evaluation model. Data collection techniques using interviews, observation, and documentation. The results showed that (1) the design component has a category that shows the role of principal leadership using management with good planning to make initial programs under the mission and vision in the learning process; (2) the installation component shows the leadership role of the principal in complementing the facilities and infrastructure as school facilities; (3) the process component shows that teaching and learning activities are following the curriculum and the role of the principal in strengthening teacher performance in learning; (4) the product component shows that the school has produced competent students.